The Impact of Working Environment on Nurses' Caring Behavior in Sabah, Malaysia - Norkiah Arsat; Bee Seok Chua; Walton Wider; Norsimah Dasan (Frontiers Media S.A., 2022)
AimsThis study aims to investigate 5 types of work environment influencing nurses' caring behavior, namely (i) participation in hospital affairs, (ii) foundations for quality of care, (iii) manager ability, leadership, and support of nurses, (iv) staffing and resource adequacy, and (v) nurse-physician relations.DesignThis research is a cross-sectional study using the survey method.MethodsData were collected from 3,532 nurses working in public hospitals and health clinics within Sabah, Malaysia in 2015. The hypothesized model was evaluated using partial least squares method.ResultsThe findings reveal that all forms of work environment have a positive effect on nurses' caring behavior except for staffing and resource adequacy which shows a negative effect on caring behavior.ConclusionOverall, this study has added to theoretical contributions in the academic and research fields as well as in practical implications in the field of nursing practice by addressing the influence of work environments on caring behavior.Implications for Nursing ManagementThe present research has provided convergent evidence on the role of the working environment in influencing the behavior of nurses working in hospitals and health clinics in Sabah, Malaysia.